Socratic Questioning to promote The Students' Critical Thinking in Reading Explanation Text (RETAIN, 2020)
Many students have a low reading habit in reading English text because the different language which cause many students could not comprehend the content of English text. This problem could lead another problem which makes the students having the low order thinking ability because the students prefer to look for the answer in the content of English text rather than understanding the content of the text. On the other hand, curriculum 2013 implemented the students-centered that requires the students becoming the active learner in thinking which needs the critical thinking ability to fulfil the requirement. To overcome about this problem, the teacher uses Socratic questioning technique. Socratic Questioning is a technique that give the students questions continually, the aim of the Socratic questioning is to help the students to think critically in comprehending the text. The implementation of Socratic questioning has 6 stages which is reading the explanation text, discussion, delivering the question, hypothesis, synthetizing, delivering the proof by giving the evidence. The teacher chooses to use the explanation text in implementing the Socratic questioning technique because the explanation text contains the explanation of why and how a phenomenon could happen. This study shows that the implementation of Socratic questioning to promote the students’ critical thinking in reading An English text especially in reading explanation text. This research Is a descriptive research which have several purposes: describing the implementation of Socratic questioning to help in promoting the students critical thinking ability in comprehending explanation text, the students response after the implementation of Socratic questioning and the students’ work which is formed in a summary after the implementation of Socratic questioning. The subject of this research is 11th graders from the state school in one of the big cities in Jawa Timur. The researcher conducted an observation and a file-recorded in implementing the Socratic questioning technique, the aim of it is to describe the implementation of Socratic questioning and how the implementation of the Socratic questioning technique to promote the students’ critical thinking. This research also did an interview for several students to explain about the students’ response after the implementation of Socratic questioning in promoting the students’ critical thinking. After that, the researcher also used the student task as in summary after the implementation of Socratic questioning. The result of this study is to show that the teacher had implemented the Socratic questioning well based on the stated theory. In addition, the result of the interview presented that students undergo the positive impact after the implementation of Socratic questioning. Furthermore, the researcher also collected the students’ task to show that the students were able to reach the highest level of taxonomy bloom which was creating the HOTS as an one of the example of HOTS, especially in summarizing.